Legal Accountability of Public Officials in Abuse of Authority: Corruption Cases in General Legal Administration - Mulyadi, Dedi; Sabila, Amani; Nadiyana, Delis Nia; firmansyah, Alif; Aulia Budiman, Eva; Salma Wirahma, Nadiyah (Intellectual Law Review (ILRE), 2025)
The purpose of this study is to analyze the limits and forms of abuse of authority committed by the Deputy Minister of Law and Human Rights (Wamenkumham) in the management of General Legal Administration (AHU), as well as to examine the role of the Corruption Eradication Commission (KPK) in supervising and handling these actions. This study uses a qualitative method with a legal-normative approach to analyze legal norms and their application in administrative governance, supplemented by a case study method for in-depth analysis of the Deputy Minister's alleged abuse of authority, supported by an analysis of relevant laws and regulations. The findings of this study indicate that the Deputy Minister's authority is coordinative and delegative in nature; actions beyond these limits can be categorized as abuse of authority. The KPK has an important role in monitoring, coordinating, and enforcing the law against such abuse of authority to maintain accountability and integrity in public administration. This study concludes that the application of good governance principles is fundamental in preventing abuse of authority in the Ministry of Law and Human Rights.